Effects of Sowing Date and Nitrogen (N) Application Rate on Grain Yield, Nitrogen Use Efficiency and 2-Acetyl-1-Pyrroline Formation in Fragrant Rice - Lihe Zhang; Congcong Shen; Shuangbing Zhu; Ningning Ren; Kai Chen; Jianlong Xu (Agronomy, 2022)
Purpose: This study aimed to assess the effects of the sowing date and nitrogen application rate on the grain yield, nitrogen use efficiency (NUE), 2-acetyl-△1-pyrroline (2-AP) contents and biochemical parameters related to 2-AP formation in fragrant rice. Methods: A factorial split-plot arrangement of treatments was set up in a split-zone experiment with two factors and three levels carried out for 3 years. The main plots included two sowing dates: April 1st and May 1st. Subplots contained three different nitrogen levels i.e., 0 kg N ha−1 (N0), 120 kg N ha−1 (N1) and 180 kg N ha−1 (N2). Results: The results indicated that compared with April 1st, the delay in the sowing date (May 1st) decreased the number of grains per panicle, 1000-grain weight, grain yield, NUE and contents of 2-AP, △1-pyrroline, proline and pyrroline-5-carboxylic acid (P5C), as well as the proline dehydrogenase (ProDH) activity. Furthermore, compared with N0, higher-N (N1 and N2) applications increased the panicle number, the number of grains per panicle, grain yield and contents of 2-AP, △1-pyrroline, proline and P5C, as well as the activities of ProDH and ornithine aminotransferase (OAT). The seed-setting rate, 1000-grain weight and NUE were decreased under N2 compared to N1, but the 2-AP content and yield were higher under the high-N application N2 (180 kg ha−1) compared to N1 (120 kg ha−1). Conclusions: Sowing on April 1st and the N2 (180 kg ha−1) application improved the yield and promoted 2-AP biosynthesis, while sowing on May 1st reduced the yield and 2-AP content. Therefore, sowing on April 1st with 180 kg ha−1 of nitrogen is the best, which can not only ensure the yield but also improve the fragrant quality of rice.